Birdwatching Track: Peluang Konservasi Burung di RPH Tambak Ngargoyoso Karanganyar Jawa Tengah - Dewi Puspita Sari; Siti Fadzillah; Wahyu Trianingsih (Universitas Khairun, 2020)
Resort Pemangku Hutan (Forest Manager Resort) or RPH Tambak is one of the forests managed by Indonesian State Forestry Enterprise in the northern part of Lawu Mountain, Surakarta. RPH Tambak located in the Berjo village, in Ngargoyoso, Central Java. This area offers ecotourism attraction for locals and international tourists. The management of forest becomes the main focus with involvement from the locals and stakeholders. This area is a potential area for avian conservation although this area is still relatively unknown. Because of its virgin forest and natural landscape, RPH Tambak has the potential to become a birdwatching spot. The aim of this research is to gather data about local avian species, to interpret the initial data for ecotourism, and to make a birdwatching track. The research methods used in this research are by tracking, and surveying the local avian species to create a roadmap for birdwatching track. The finding of this research is there are 40 species of birds from 25 families living along as cosmopolite and rarely in the birdwatching track. The birdwatching track has 5 posts with different specifications (vegetation, altitude, and tracking time) and tracking distance to make various contact with local avian species. The birdwatching track will be maintained by locals that has the access to the peak of the Lawu Mountain.